2013
DOI: 10.3892/mco.2013.201
|View full text |Cite
|
Sign up to set email alerts
|

Middle and lower esophagectomy preceded by hand-assisted laparoscopic transhiatal approach for distal esophageal cancer

Abstract: Abstract. Respiratory morbidity is the most frequent complication following an esophagectomy. This study was designed to determine the efficacy of middle and lower esophagectomies preceded by the hand-assisted laparoscopic transhiatal approach (LTHA) regarding the perioperative outcomes of distal esophageal cancer. The esophageal hiatus was opened and carbon dioxide was introduced into the mediastinum. Dissection of the distal esophagus was performed up to the level of the tracheal bifurcation. En bloc dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…There were some suggestions that hand-assisted laparoscopic transhiatal approach has several advantages over the thoracoscopic approach in patients with middle and lower esophageal cancer. Shiozaki et al [25] demonstrated that thoracic trauma was minimized and duration of one-lung ventilation was reduced with this procedure. Also, it enables easy access to the posterior mediastinal lymph nodes, including the para-aortic and left pulmonary ligament lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…There were some suggestions that hand-assisted laparoscopic transhiatal approach has several advantages over the thoracoscopic approach in patients with middle and lower esophageal cancer. Shiozaki et al [25] demonstrated that thoracic trauma was minimized and duration of one-lung ventilation was reduced with this procedure. Also, it enables easy access to the posterior mediastinal lymph nodes, including the para-aortic and left pulmonary ligament lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported about the usefulness of intraoperative recurrent laryngeal nerve monitoring to prevent PRNP (23,24). Recently, our group have established a new surgical technique, laparoscopic transhiatal esophagectomy without thoracoscopic procedure, to achieve less invasiveness (25)(26)(27) and reported a lower incidence of PRNP in patients with laparoscopic transhiatal esophagectomy (28). Further studies with a larger number of patients appear essential to emphasize this conclusion.…”
Section: Discussionmentioning
confidence: 91%
“…It is reported that laparoscopic transhiatal manipulation is possible up to the middle esophagus [16]. With the progress in laparoscopic surgery [17], laparoscopic transhiatal esophagomyotomy for esophageal motility disorder even in the superior portion could be performed safely.…”
Section: Discussionmentioning
confidence: 99%